The Influence of the Drying Process on the Quality of Lamtoro Seed Cruckers (Leucaena leucocephala - Jublina Bakoil (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine one of the lamtoro cracker drying treatments that can produce quality crackers. The research method used was a Completely Randomized Design (CRD) with 4 treatments and each treatment was repeated 3 times to obtain 12 experimental units. The treatments tried in this study were a) 1 day drying time; b) Drying time 2 days; c) Drying time 3 days; and d) 4 days drying time. The treatment was carried out simply randomly by drawing a lottery to avoid subjectivity in placing the experimental unit. The order of placement of the treatments on the trial plan is the order in which the experiment is carried out. The results showed that there was a very significant effect on color, aroma, texture and taste with a drying time of 2 days which was the best treatment so that it produced the best quality because it gave the impression of color, aroma, texture and taste that the panelists liked